Legal Politics of Extension of Term of Village Head - Ibrahim Ibrahim; Ismaidar Ismaidar; Tamaulina Br Sembiring (International Journal of Sociology and Law, 2025)
The extension of the term of office of the village head was motivated by a demonstration by almost all village heads throughout Indonesia who expressed their wishes and aspirations in front of the building of the People's Representative Council of the Republic of Indonesia, so that the term of office of the village head would be revised to be extended. This study aims to determine how the political legal turmoil caused by the extension of the village head's term of office in accordance with Law Number 3 of 2024 concerning Villages. By using a qualitative literature study method, this study analyzes more relevant literature to understand the influence of legal politics on the extension of the village head's term of office